Trybunalskie i sądowe stosowanie zasady „ignorantia iuris nocet” na gruncie praktyki orzeczniczej w Polsce - Woś, Tomasz (Filozofia Publiczna i Edukacja Demokratyczna, 2018)
The article discusses the issue of the Constitutional Court’s and other courts’ application of the principle of ignorantia iuris nocet in the practice of issuing rulings. Based on the analysis of the case law, it presents the Constitutional Court’s standpoint concerning the role of the principle of ignorantia iuris nocet in the Polish system of law and its application in the Constitutional Court’s case law. At the same time, it discusses other courts’ application of this principle, i.e. its influence on the decision-making processes of the application of law by the Supreme Court, courts of appeal and administrative courts. The analysis of the case law show that the principle of ignorantia iuris nocet plays a special role in the Polish system of law. In their decisions, both the Constitutional Court and other courts concerned emphasise that the Polish system of law, like other contemporary systems of law, is based on this principle, and its violence would lead to unpredictable results in the practice of issuing rulings. There are no major differences between the application of the principle of ignorantia iuris nocet by the Constitutional Court and other courts concerned. In cases involving the ignorance of the law, both the Constitutional Court and other courts commonly recognise and apply, within the scope of their competence, the principle of ignorantia iuris nocet. Administrative law takes a particular stance on the application of this principle. In the Supreme Administrative Court’s judicature, a jurisdictional approach has been adopted that recognises that the operation of this principle is reduced in administrative procedure. In turn, the study of the case law of provincial administrative courts shows that these courts still have not adopted a uniform jurisdictional pattern in this respect.